2008
DOI: 10.1038/icb.2008.99
|View full text |Cite
|
Sign up to set email alerts
|

Type II‐activated macrophages suppress the development of experimental autoimmune encephalomyelitis

Abstract: Treatment with immune complexes, which ligate Fcc receptors (FccRs), suppresses the development of experimental autoimmune encephalomyelitis (EAE). To determine the mechanism of action, we investigated how these immune complexes affected type II activation of macrophages (that is, exposure to immune complexes in a proinflammatory environment). Our results show that lower doses of interferon-c (IFN-c) were more effective at priming bone marrow-derived macrophages (BMM/) to produce more interleukin 10 (IL-10) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
149
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(171 citation statements)
references
References 27 publications
16
149
2
Order By: Relevance
“…Analysis of the spinal cord of treated mice showed that SHED-CM induced a shift in the macrophage phenotype from an M1 proinflammatory phenotype to an M2 anti-inflammatory phenotype, as well as suppressed the expression of proinflammatory mediators. Treatments resulting in shifts from M1 to M2 phenotypes were shown to suppress EAE (37,38). In addition, our in vitro analysis indicated that the presence of SHED-CM inhibited the proliferation of…”
Section: Discussionmentioning
confidence: 80%
“…Analysis of the spinal cord of treated mice showed that SHED-CM induced a shift in the macrophage phenotype from an M1 proinflammatory phenotype to an M2 anti-inflammatory phenotype, as well as suppressed the expression of proinflammatory mediators. Treatments resulting in shifts from M1 to M2 phenotypes were shown to suppress EAE (37,38). In addition, our in vitro analysis indicated that the presence of SHED-CM inhibited the proliferation of…”
Section: Discussionmentioning
confidence: 80%
“…Cell-based therapies constitute a promising approach in which cells are differentiated into an immunosuppressive or regulatory phenotype and administered into patients. Experimentally, macrophages have been evaluated as good candidates for cell-based therapeutic intervention not only for atopic and autoimmune diseases, but also for the treatment of kidney diseases (18)(19)(20)(21)(22)(23)(24). Furthermore, regulatory macrophages have been successfully applied to human transplantation patients in first clinical trials to interfere with overt immune responses (25,26) and are discussed as a future therapy in solid-organ transplantation and beyond (27).…”
Section: Discussionmentioning
confidence: 99%
“…Activated macrophages can be broadly classified into classically activated M1 macrophages and alternatively activated macrophages (AAMs or M2). While M1 macrophages are associated with pathologic CNS inflammation in EAE and MS development, M2 macrophages are protective against EAE [13]. IL-33 has recently been shown to promote Th2-cell expansion and skew M1 to the M2 phenotype [14].…”
Section: Introductionmentioning
confidence: 99%